2014
DOI: 10.1080/16184742.2014.880496
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived interactivity and web organization on user attitudes

Abstract: Research question: This study sought to answer the following research question: What are the significant determinants influencing online users' attitudes to sports websites? Specifically, this investigation examined (1) the direct and indirect effects of web content and perceived interactivity and (2) the moderating effect of web organization on attitudes.Research methods: Respondents (N = 329) from a large university in the USA were utilized to test a conceptual model in this study. Structural Equation Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
1
19
0
2
Order By: Relevance
“…When users can pan, swipe, zoom-in, and drag virtual objects on the website, they involve greater number of sensory channels to process the information (Reeves & Nass, 2000), which provides greater immersion into the stimulus (Beuckels & Hudders, 2016; Oh & Sundar, 2015). Especially, perceived interactivity has been shown to play a significant role in predicting feelings of immersion (Lee & Chung, 2013) and greater user attitudes toward the website and its content (T. Ahn et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When users can pan, swipe, zoom-in, and drag virtual objects on the website, they involve greater number of sensory channels to process the information (Reeves & Nass, 2000), which provides greater immersion into the stimulus (Beuckels & Hudders, 2016; Oh & Sundar, 2015). Especially, perceived interactivity has been shown to play a significant role in predicting feelings of immersion (Lee & Chung, 2013) and greater user attitudes toward the website and its content (T. Ahn et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…interactions among fans who share a common interest with the team; Chan and Li, 2010), team-to-fan relationship (i.e. fans' behaviours arising from the actions of the team; Ahn et al, 2014) and fan co-creation (i.e. interactions among fans aimed at increasing the value of the team for them; Uhrich, 2014).…”
Section: Conceptualisation Of the Model Fan Engagement Through Snsmentioning
confidence: 99%
“…In this study, the concept of team-to-fan relationship in SNS is linked to an interactive relationship created by the team 166 IJSMS 20,1 aimed at building a long-term relationship with fans (Hsiao et al, 2015). Ahn et al (2014) further proposed that professional sport organisations should increasingly focus on creating dynamic SNS (e.g. relevant information, improved design and entertainment possibilities) to drive traffic and to maintain a strong interactive relationship with their fans.…”
Section: Conceptualisation Of the Model Fan Engagement Through Snsmentioning
confidence: 99%
“…Several empirical studies indicated that perceived interactivity positively influences the attitude towards the website (Ahn, Hong, & Pedersen, 2014;Cho & Leckenby, 1999;Hwang & McMillan, 2002;Jee & Lee, 2002;McMillan et al, 2003;Schlosser, 2003;Song & Zinkhan, 2008;Wu, 2000;Yoo & Stout, 2001). On the other hand, the findings of the studies, which investigated the relationship between actual interactivity and the attitude towards the website, were inconsistent as some studies found that actual interactivity positively influences the attitude towards the website (Boushra, 2008;Fiore & Jin, 2003) while others indicated a mixed or negative impact (Bezjian-Avery et al, 1998;Bucy, 2004;Coyle & Thorson, 2001;Fortin & Dholakia, 2005;Massey & Levy, 1999;Sundar, 2000;Sundar et al, 2003).…”
Section: Attitude Towards the Websitementioning
confidence: 99%